Music and social change in South Africa : maskanda past and present - Olsen, Kathryn, 1957- (Temple University Press, 2014)
Music and Social Change in South Africa looks at contemporary maskanda-a folk musical genre distinguished by fast guitar picking and blues-style vocal intonation-against the backdrop of South Africa''s history. A performance practice that emerged in the early decades of the twentieth century among Zulu migrant workers, maskanda is strongly associated with young Zulu men''s experiences of repression and dislocation during imperial and, more particularly, apartheid rule. Working closely with translated song lyrics and musical notation-and applying musical and socio-political analysis to this mus.